2023
DOI: 10.3389/fimmu.2023.1007626
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation and exhaustion marker expression on T-cell subsets in ART-treated adolescents and young adults with perinatal HIV-1 infection as correlates of viral persistence

Abstract: HIV-1 infection in memory CD4+ T cells forms a latent reservoir that is a barrier to cure. Identification of immune biomarkers that correlate with HIV-1 reservoir size may aid with evaluating efficacy of HIV-1 eradication strategies, towards ART-free remission and cure. In adults living with non-perinatal HIV-1, the immune exhaustion marker PD-1 on central memory CD4+ T cells (Tcm) correlates with measures of HIV-1 reservoir size. Immune correlates of HIV-1 are less defined in adolescents and young adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The results of this study provide evidence to support consideration of ADCC activity as an immune outcome measure in these trials. While our observation that gp120-specific ADCC activity inversely correlates only with levels of defective provirus, an intervention capable of targeting cells with defective provirus could still prove useful in decreasing the overall number of cells capable of contributing to chronic immune activation during long-term ART [10,[29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The results of this study provide evidence to support consideration of ADCC activity as an immune outcome measure in these trials. While our observation that gp120-specific ADCC activity inversely correlates only with levels of defective provirus, an intervention capable of targeting cells with defective provirus could still prove useful in decreasing the overall number of cells capable of contributing to chronic immune activation during long-term ART [10,[29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 73%
“…Despite viral suppression on ART, people living with HIV tend to have increased immune activation and inflammation markers [16][17][18] which are associated with a litany of adverse health outcomes such as cardiovascular disease [19,20], neurological disorders [21], diabetes [22], cancer [23,24], and accelerated aging [25][26][27][28]. Cells harboring HIV provirus, whether intact or defective [10,[29][30][31][32][33], are drivers of this chronic immune activation due to their ability to persistently produce and present viral antigens [34], with the size of the reservoir positively associated with inflammation markers [35,36] and risk of comorbidities [21]. Additionally, several studies have demonstrated an inverse relationship between HIV reservoir size and time to viral rebound upon ART interruption, fueling speculation that a functional cure for HIV may be possible by limiting the reservoir's size [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Our results, derived from the largest sample size reported to date, reveal specific methylation Consistent with previous findings 15 , we found that the majority of the integrated DNA proviruses were defective. Recent studies have reported that both intact and defective integrated HIV-1 DNA proviruses remain transcriptionally active under suppressive ART, contributing to prolonged immune activation [33][34][35] and greater comorbidity among PWH. Epigenetic regulation of host factors plays a critical role in HIV-1 transcriptome activation and silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in adults living with HIV-1 have demonstrated the heightened decay of cells harboring replication-competent intact proviruses and potentially replication-competent over those harboring defective proviruses [46,47]. In both adult and pediatric populations, intact proviruses levels positively correlate with total HIV-1 cpm CD4 þ T cells [46,48]. The advent of newer multiplex HIV-1 DNA assays optimized for different HIV-1 subtypes will be instrumental for identifying the composition of the proviral pool capable of eliciting rebound after ATI.…”
Section: Limitations Of Total Hiv-1 Dna Measurementsmentioning
confidence: 99%